Impact of Breast Cancer Subtypes on Prognosis of Women with Operable Invasive Breast Cancer: A Population-based Study Using SEER Database - Hwang, Ki-Tae; Kim, Jongjin; Jung, Jiwoong; Chang, Ji Hyun; Chai, Young Jun; Oh, So Won; Oh, Sohee; Kim, Young A; Park, Sung Bae; Hwang, Kyu Ri (Clinical cancer research, 2019)
To determine the prognostic roles of breast cancer subtypes in females with operable invasive breast cancer. Data of 321,958 patients from Surveillance, Epidemiology, and End Results (SEER) database were analyzed. Breast cancer subtypes were classified into four categories according to the status of hormone receptor (HRc) and HER2: HRc(+)/HER2(-), HRc(+)/HER2(+), HRc(-)/HER2(+), and HRc(-)/HER2(-). Proportions of HRc(+)/HER2(-), HRc(+)/HER2(+), HRc(-)/HER2(+), HRc(-)/HER2(-), and unknown subtype were 70.3%, 9.4%, 3.9%, 10.4%, and 6.0%, respectively. HRc(+)/HER2(-) showed the highest 5-year breast cancer-specific survival (BCSS) rate (95.5%), followed by HRc(+)/HER2(+) (94.1%), HRc(-)/HER2(+) (89.3%), and HRc(-)/HER2(-) (83.1%). HRc(+)/HER2(-) and HRc(+)/HER2(+) showed higher 5-year overall survival (OS) rates (88.4% and 88.2%, respectively) than HRc(-)/HER2(+) and HRc(-)/HER2(-) (83.9% and 76.5%, respectively). HRc(-)/HER2(-) showed the worst BCSS irrespective of race, age, or stage. Although proportions of HRc(-)/HER2(-) in the subgroup with negative event regarding BCSS and OS were 10.4% and 10.2%, respectively, they were 34.2% and 22.7%, respectively, in the subgroup with positive event. Subtype was a significant factor in both univariable and multivariable analyses regarding both BCSS and OS (all < 0.001). Breast cancer subtype was a significant independent prognostic factor regarding both BCSS and OS in multivariable analyses. HRc(+) subtypes showed better prognosis compared with HRc(-) subtypes regarding both BCSS and OS. HRc(-)/HER2(+) showed better prognosis than HRc(-)/HER2(-) but worse prognosis than HRc(+) subtypes regarding both BCSS and OS. The triple-negative subtype showed the worst BCSS compared with the other subtypes irrespective of race, age, or stage.